Sustainability of Village-Owned Enterprises for Economic Development of Lombok Utara - Putu Somiartha; Made Sudarma; Ni Luh Putu Anom Pancawati; Ni Nyoman Satya Widari; Nengah Sukendri (Khazanah Sosial, 2024)
This research aims to analyze the direct and indirect effects of managerial competency characteristics, marketing mix, social capital, and the sustainability of Badan Usaha Milik Desa (Village-Owned Enterprises, BUM Desa) enterprises on economic development in Lombok Utara Regency. Additionally, examines the social capital determinants that moderate the impact of managerial competency on the sustainability of BUM Desa enterprises in Lombok Utara Regency. This study employs an associative quantitative research design. This research was carried out in 43 villages within Lombok Utara Regency, with a total sample of 215 from 43 BUM Desas across these villages. The SEM-PLS method is employed for data analysis. The research findings indicate that management competency, marketing mix, social capital, and the sustainability of BUM Desa enterprises do not significantly influence the performance of village development in Lombok Utara Regency. Social capital significantly moderates the impact of managerial ability on the success of BUM Desa. The findings of this research are anticipated to enhance theoretical understanding of the mechanisms of social capital, particularly how prolonged retention greatly moderates the impact of managerial competency on the performance of BUM Desa.